2020
DOI: 10.1038/s41413-020-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Axin1 in osteoblast precursor cells leads to defects in postnatal bone growth through suppressing osteoclast formation

Abstract: Axin1 is a negative regulator of β-catenin signaling and its role in osteoblast precursor cells remains undefined. In the present studies, we determined changes in postnatal bone growth by deletion of Axin1 in osteoblast precursor cells and analyzed bone growth in newborn and postnatal Axin1 Osx mice and found that hypertrophic cartilage area was largely expanded in Axin1 Osx KO mice. A larger number of chondrocytes and unabsorbed cartilage matrix were found in the bone marrow cavity of Axin1 Osx KO mice. Oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
1
10
1
Order By: Relevance
“…Here, our study showed that deletion of BK channels in osteoblasts induced decreases in β-catenin expression in both bone tissues and primary osteoblasts. The inhibition of β-catenin in osteoblasts leads to an increase in osteoclast formation (Shu et al, 2020); however, trap staining in the trabecular regions showed no significant difference in our study. Runx2 is the main transcription factor in the process by which MSCs differentiate into osteoblasts.…”
Section: Discussioncontrasting
confidence: 87%
“…Here, our study showed that deletion of BK channels in osteoblasts induced decreases in β-catenin expression in both bone tissues and primary osteoblasts. The inhibition of β-catenin in osteoblasts leads to an increase in osteoclast formation (Shu et al, 2020); however, trap staining in the trabecular regions showed no significant difference in our study. Runx2 is the main transcription factor in the process by which MSCs differentiate into osteoblasts.…”
Section: Discussioncontrasting
confidence: 87%
“…CSF-1, OPG, and AXIN1 are important for bone homeostasis, where CSF-1 is released by osteoblasts to directly induce osteoclastogenesis 81 . In contrast, OPG suppresses osteoclastogenesis, and its expression is upregulated by osteoblasts through β-catenin signalling 82 , which has recently been shown to be inhibited by AXIN1 83 . The exact mechanisms for the downregulation of these proteins, their interactions, and how they impact host response to PJI is unknown and warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…In the fracture healing process, osteoclasts play an important role in the formation of new bones. In this process, the apoptosis of hypertrophic chondrocytes and resorption of the mineralized cartilage matrix by osteoclasts occurs, and is then replaced by new bone at the site of absorption 36 38 . Therefore, the active roles of both osteoblasts and osteoclasts are required for a successful fracture healing process.…”
Section: Discussionmentioning
confidence: 99%